A Randomized Cross-over Study on the Effects of Levonorgestrel- and Desogestrel-containing Oral Contraceptives on the Anticoagulant Pathways - Tans, Guido; Curvers, Joyce; Middeldorp, Saskia; Thomassen, M. Christella L. G. D.; Meijers, Joost C. M.; Prins, Martin H.; Bouma, Bonno N.; Büller, Harry R.; Rosing, Jan (Thrombosis and Haemostasis, 2000)
The use of oral contraceptives (OC) causes disturbances of the procoagulant, anticoagulant and fibrinolytic pathways of blood coagulation which may contribute to the increased risk of venous thrombosis associated with OC therapy. Here we report the results of a cyclecontrolled randomized cross-over study, in which we determined the effects of so-called second and third generation OC’s on a number of anticoagulant parameters. In this study, 28 non-OC using women were randomly prescribed either a second generation (150 µg levonorgestrel/30 µg ethinylestradiol) or a third generation OC (150 µg desogestrel/30 µg ethinylestradiol) and who switched to the other OC after a two month wash out period. The anticoagulant parameters determined were: antithrombin (AT), α2-macroglobulin (α2-M), α1-antitrypsin, protein C inhibitor (PCI), protein C, total and free protein S and activated protein C sensitivity ratios (APC-sr) measured with two functional APC resistance tests which quantify the effect of APC on either the activated partial thromboplastin time (aPTT) or on the endogenous thrombin potential (ETP). During the use of desogestrel-containing OC the plasma levels of αc2-M, α1-antitrypsin, PCI and protein C significantly increased, whereas AT and protein S significantly decreased. Similar trends were observed with levonorgestrel-containing OC, although on this kind of OC the changes in AT, PCI and protein S (which was even slightly increased) did not reach significance. Compared with levonorgestrel, desogestrel-containing OC caused a significant decrease of total (p <0.005) as well as free protein S (p <0.0001) and more pronounced APC resistance in both the aPTT (p = 0.02) and ETPbased (p <0.0001) APC resistance tests. These observations indicate that the activity of the anticoagulant pathways in plasma from users of desogestrel-containing OC is more extensively impaired than in plasma from users of levonorgestrel-containing OC.
Keywords: Oral contraceptives; haemostasis; thrombosis